Duty Bearer-Right Holder in Law Number 4 Year 2024 on Maternal and Child Welfare in The First Thousand Days of Life Phase - Haryani, Tiyas Nur (Jurnal Ekonomi Kependudukan dan Keluarga, 2025)
Law No. 4 Year 2024 on Maternal and Child Welfare in the First Thousand Days of Life has been promulgated by the government of the Republic of Indonesia. The regulation guarantees the implementation and fulfilment of the needs of mothers and children in order to improve the quality of human resources. This article aims to map the duty-bearers-rights holders in the draft law on maternal and child welfare in the first thousand days of life. Analysing the position of maternal mothers is the main focus of this research, as maternal mothers are the main subjects in the draft law on maternal and child welfare in the first thousand days of life. Articles were analysed by context review from secondary data sources of Law No. 4 of 2024 on Maternal and Child Welfare in the First Thousand Days of Life and publication documents with the keywords ‘duty bearers’, ‘rights holders’, ‘maternal welfare’ and ‘maternal and child health’. The results show that most maternal mothers have a dual status as rights holders as well as duty bearers in their duties and responsibilities as pregnant women and newborns in Law No. 4 of 2024 on Maternal and Child Welfare in the First Thousand Days of Life.